Estrategia de diferenciación para la exportación de piña al mercado de Estados Unidos. - Tinoco Monserrate, Leydi Patricia (My University, 2019)
Pineapple is a recognized fruit because of its nutritional benefits, delicious taste and the ability to adapt to different climates, which makes it easy to handle in its cultivation. With a tropical climate produces this fruit, but just few of them produce it with export quality, due to the implementation of strategies for both cultivation and marketing generated by the government, marketers and producers. Pineapple is mostly consumed in the United States, Japan, Chile and the United Kingdom markets generating a significant demand worldwide. For 20 years, Ecuador has exported a considerable average of golden sweet export pineapple that stands out for its sweet taste and low levels of acidity. This variety has reached europeans and american countries and is produced mainly in provinces and towns of the center and coastal areas of Ecuador. The main destination of the fruit is Chile where most of the national production is sold, followed by Belgium, Germany and Argentina, some time ago the United States was the main destination. Today, the United States shows a growth in pineapple import levels, and it is estimated that per capita consumption of this fruit among Americans has increased in recent years, so being a country with a history of pineapple consumption from Ecuador. The ecuadorian producers should take advantage of the existence of differentiation strategies to recover the market, as a result this research explains the dynamics of pineapple trade towards the United States , using concepts and estates on differentiating strategies depending on the characteristics of the information that supports the research, and the methods are exploratory and descriptive.
La piña es un fruto reconocido por sus beneficios nutricionales, además de su delicioso sabor y su capacidad de adaptación a distintos climas, lo que hace de fácil manejo en su cultivo. Esta fruta es producida en muchos países de clima tropical, son pocos los países que la producen con calidad de exportación, mediante la implementación de estrategias tanto para el cultivo como para la comercialización que se generan desde el gobierno, los comercializadores y productores. Desde hace 20 años, Ecuador ha exportado un promedio considerable de piña tipo golden sweet sobresale por su sabor dulce y bajos niveles de acidez. El principal destino de la fruta es Chile donde se vende la mayoría de la producción, seguido de Bélgica, Alemania y Argentina, algún tiempo atrás Estados Unidos era principal destino. Hoy, Estados Unidos muestra un crecimiento en los niveles de importación de piña, y se estima que el consumo per cápita de ésta fruta entre los estadounidenses ha aumentado en los últimos años por lo que, siendo un país con antecedentes de consumo de piña proveniente del Ecuador, los productores ecuatorianos deberían aprovechar la existencia de estrategias de diferenciación para recuperar el espacio perdido, para ellos a través de este trabajo de titulación se analiza la dinámica del comercio de piña hacia los Estados Unidos, recurriendo a conceptos y estamentos sobre las estrategias diferenciadoras en función de las características de la información que sustenta la investigación, se aplicará el método exploratorio y descriptivo para el desarrollo de la investigación.
Keywords: COMPETITIVIDAD; TIPOS DE ESTRATEGIAS; ESTRATEGIA DE DIFERENCIACIÓN; EXPORTACIÓN DE PIÑA